Routine Core Analysis (RCAL) Untuk Menentukan Porositas, Permebilitas, dan Saturasi Pada Batupasir (Sandstone) - Arief Rahman (Publikasi Indonesia, 2022)
The physical properties of basic reservoir rocks that are very important to know, especially in the oil and gas industry, include porosity, permeability and saturation. The three physical properties determine the economics of an oil and gas field, especially in the reservoir rock layer. Sandstone (sand) is a lithology that very common oil and gas reservoir rock. The research was conducted at a laboratory scale using three (3) core plug samples from conventional cores. The method used in the Porosity measurement is Boyle's law helium porosimeter, while for the measurement of saturation using the results of the Conventional Retort method. The results of his research are the porosity values of the three samples taken from an average value of 23.76%, which is in the very good (very good) category. Meanwhile, the permeability values of the three samples were taken from an average value of 211.67 mD which is also in the very good category. From the graph of porosity to permeability it shows a directly proportional relationship, then from the graph of porosity to depth of the three samples above it shows an inverse relationship, those are shown by the trendline but with a very low R2 value. This is possibly caused by two things, namely: lack of sample data, and too close sample interval so that it cannot be used as justification that porosity and depth are not reversed. Oil saturation values (So) and gas saturation (Sg) of the three samples were taken from the average values of 46% and 1.7%.